Volunteering with sex offenders: the attitudes of volunteers toward sex offenders, their treatment and rehabilitation - Kerr, N.; Tully, R.; Völlm, Birgit (SAGE Publications, 2017)
The general public has been shown to hold negative attitudes toward sexual offenders (Levenson, Brannon, Fortney, & Baker, 2007; Willis et al., 2010), sex offender treatment (e.g. Olver & Barlow, 2010) and the rehabilitation of sexual offenders (Payne, Tewksbury, & Mustaine, 2010). It appears pertinent to the success of sex offender management strategies that utilise volunteers that selected volunteers do not share these attitudes. Here, volunteers for Circles of Support and Accountability (CoSA), a community-based initiative supporting the reintegration of sex offenders, completed three validated psychometric measures assessing attitudes toward sex offenders in general and toward their treatment and rehabilitation. Responses were compared to a UK general public sample. The results showed that volunteers held more positive attitudes toward sex offenders, sex offender treatment and sex offender rehabilitation than the UK general public sample. The significance of these findings is discussed alongside directions for future research.